Antiques maul - Allan, Barbara (Allan, Barbara. Trash 'n' treasures mystery., 2007)
Newly divorced Brandy Borne has an idea for preserving her sanity and keeping her mother busy: their own booth at the new antiques mall. When a body is found at the mall, the police blame the victim's dog, but Brandy thinks the dog has been framed.